2017
DOI: 10.1177/0020764017717283
|View full text |Cite
|
Sign up to set email alerts
|

Lay beliefs about the causes and cures of schizophrenia

Abstract: Overall, laypeople have reasonably accurate beliefs and a multidimensional view of the causes and treatments of schizophrenia. Nevertheless, our results suggest that public education about the etiology and treatment of schizophrenia are necessary to increase actual usage of mental health services and treatments for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The odds of seeking medical help for schizophrenia among students and unemployed were higher than farmers or housewives. This finding was supported by a study conducted in Saudi [ 6 ]. This might be due to as an individual's educational status increases their level of understanding about mental health improved and their perception towards mentally ill will become positive.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The odds of seeking medical help for schizophrenia among students and unemployed were higher than farmers or housewives. This finding was supported by a study conducted in Saudi [ 6 ]. This might be due to as an individual's educational status increases their level of understanding about mental health improved and their perception towards mentally ill will become positive.…”
Section: Discussionsupporting
confidence: 80%
“…The general population in different countries had a different perception of schizophrenia. However, people living in western countries focus mainly on biological such as genetics, disease of the brain, and infection, and social risk factors such as personal weakness [ 4 , 5 , 6 ]. A study conducted in the united kingdom showed that emotional state could cause schizophrenia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we will first discuss the possible causes of schizophrenia symptoms and how knowing them can lead to a successful holistic management of the disorder. There is no single cause of schizophrenia though several factors have been identified (Park, Lee, Furnham, Jeon, & Ko, 2017). As mentioned above, the probability of developing schizophrenia was found to be larger in males than females (Aleman et al, 2003;McGrath et al, 2008).…”
Section: Possible Causes Of Schizophreniamentioning
confidence: 91%
“…Moreover, only about 20% among those diagnosed with a mental disorder received help from a mental health professional [2], which is much lower than the rate observed in New Zealand (38.9%), the U.S. (43.1%), Spain (35.5%), Belgium (39.5%), and Australia (34.9%) [34][35][36]. Moreover, a previous study [37] emphasized the need for education on etiology and treatment regarding schizophrenia in Korea to guide patients to use mental health services. Further, sex and personality traits should be considered when providing education to promote help-seeking behavior [38].…”
Section: Plos Onementioning
confidence: 99%